(3hHd GdZeGe ajef RhLg GdfHi Ydjg GdSdGes - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg hHd GdZeGe ajef RhLg GdfHi Ydjg GdSdGe hgh eG CNHQfG Hg GdeMOK fGUQ CHh YHO Gddg s
(3BNQgG (B:s
(3hPcQ CHh GdaQL Hf GdLhRi ai efGbH RjO Hf MGQKI Cfg RhL GdfHi Udi Gddg Ydjg hSde RjfH HfJ LMT s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs